LEGAL PROTECTION FOR OUTSOURCED WORKERS WHO ARE LAID OFF DURING THE PERIOD OF THE EMPLOYMENT AGREEMENT - Khotim; Hufron (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
The implementation of Law Number 6 of 2023 concerning the Stipulation of Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation into Law (UUCK) has brought fundamental changes to the employment regime, particularly regarding Fixed-Term Employment Agreements (PKWT) and the outsourcing system. Outsourced workers bound by PKWT are a vulnerable group whose position is increasingly dilemmatic post-UUCK. Significant normative conflicts arise regarding compensation rights due to unilateral termination of employment (PHK) before the PKWT contract expires. Law Number 13 of 2003 (UUK) explicitly requires compensation payments equal to the remaining wages of the contract period. In contrast, Article 61A of the UUCK and Government Regulation Number 35 of 2021 (PP 35/2021) only regulate the provision of compensation based on the length of service. This radical difference in the calculation of rights creates severe legal uncertainty and has the potential to violate the principles of justice and benefit for workers. This normative legal research aims to: 1) Critically analyze the conflicting norms arising from Article 62 of the UUK and Article 61A of the UUCK/PP 35/2021 regarding compensation for termination of PKWT (non-permanent employment contract) contracts. 2) Formulate a concept for an ideal legal protection arrangement, guaranteeing the constitutional rights of PKWT outsourced workers to a decent living and legal certainty. This research uses a statutory, conceptual, and comparative legal approach. The study findings indicate that the partial implementation of UUCK/PP 35/2021 without considering the spirit of Article 62 of the UUK actually worsens protection conditions, triggering labor market flexibility that is too biased towards employers. The proposed ideal concept is a harmonization that requires employers to pay compensation for PKWT (exceeded employment period) plus compensation equal to the remaining wages of the unexpired contract period, if the termination is carried out unilaterally without valid reasons. This protection must be enforced by strengthening the role of the Industrial Relations Court (PHI) and pro-worker labor supervision